Documents written by the heads of the Catechetical School in Alexandria: From Mark to Clement - Oliver, Willem H. (Verbum et ecclesia, 2017)
The Catechetical School in Alexandria has delivered a number of prolific scholars and writers during the first centuries of the Common Era, up to its demise by the end of the 4th century. These scholars have produced an extensive collection of documents of which not many are extant. Fortunately, there are many references to these documents supplying us with an idea of the content thereof. As the author could not find one single source containing all the documents written by the heads of the School, he deemed it necessary to list these documents, together with a short discussion of it where possible. This article only discusses the writings of the following heads: Mark the Evangelist, Athenagoras, Pantaenus and Clement, covering the period between approximately 40 CE and the end of the 2nd century. The follow-up article discusses the documents of the heads who succeeded them.Intradisciplinary and/or interdisciplinary implications: The potential results of the proposed research are a full detailed list of all the documents being written by the heads of the School in Alexandria. The disciplines involved are (Church) History, Theology and Antiquity. These results will make it easier for future researchers to work on these writers.